Manajemen Pendidikan Vokasi Maritim dalam Perspektif Human Capital - Suprapti, Fitri; Wahyuni, Eni Tri; Hermawati, Renny (Majalah Ilmiah Gema Maritim, 2025)
Maritime vocational education plays a strategic role in preparing competent, professional, and competitive seafarers. However, nautical education management is often oriented toward fulfilling curriculum requirements and certification standards, without viewing cadets as strategic human capital. This study aims to analyze maritime vocational education management from a human capital perspective, particularly in developing the work readiness of Diploma IV Nautical graduates. A qualitative research method with a case study approach was employed at a state maritime polytechnic. Data were collected through in-depth interviews with 12 informants consisting of institutional leaders, nautical lecturers, simulator instructors, senior cadets, and alumni working in the shipping industry. Data were enriched through observation of learning processes in classrooms, simulators, and training vessels, as well as analysis of curriculum documentation and academic policies. Data analysis used thematic analysis with NVivo 12 software. The findings indicate that maritime vocational education management focuses primarily on regulatory compliance and STCW certification, while human capital development—such as long-term competence value, critical thinking, and safety culture—has not been optimally integrated. This study recommends strengthening human capital-based education management to sustainably enhance the quality and competitiveness of nautical graduates.